2005
DOI: 10.1038/sj.ejcn.1602262
|View full text |Cite
|
Sign up to set email alerts
|

Greater than predicted decrease in resting energy expenditure with age: cross-sectional and longitudinal evidence

Abstract: Objective: To determine whether the age-related decrease in resting energy expenditure (REE) is explained by variations in body composition. Design: In Study 1, adult subjects (20-70 years) from the Québec Family Study were classified into five different age groups. Body composition was measured by hydrodensitometry to determine fat mass and fat-free mass as predictors of REE. In the youngest group of individuals these predictors were used to plot a reference regression that was then used to predict REE in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Cross‐sectional and longitudinal evidence from Alfonzo‐Gonzalez et al. confirms that resting EE is affected by age independent of changes in body composition and that this decrease is more pronounced in early adulthood in men but in the later years of women (42).…”
Section: Discussionmentioning
confidence: 92%
“…Cross‐sectional and longitudinal evidence from Alfonzo‐Gonzalez et al. confirms that resting EE is affected by age independent of changes in body composition and that this decrease is more pronounced in early adulthood in men but in the later years of women (42).…”
Section: Discussionmentioning
confidence: 92%
“…Age-related declines in resting energy expenditure are not observed among those women that exercise regularly [ 89 ]. Thus, continuous physical activity during the mid-life may be an efficacious strategy to counteract the age-related [ 166 ] and menopause-related decreases [ 89 ] in resting energy expenditure and prevent weight gain and abdominal adiposity deposition. In fact, a recently published meta-analysis of 8 walking intervention studies among peri- and postmenopausal women demonstrated statistically significant improvements in BMI, body weight, and body fat percentage as compared to no-exercise groups [ 167 ].…”
Section: Implications For Therapymentioning
confidence: 99%
“…As described by the investigators, this large metabolic adaptation could not be attributed to the fact that RMR was measured with a different calorimeter 6 years after the end of the competition. Additionally, our research experience reveals that the reported persistent metabolic adaptation can only be partly attributable to an aging effect over a 6‐year follow‐up .…”
mentioning
confidence: 78%